2018
DOI: 10.1038/s41598-018-36023-w
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone-Induced Odor Associative Fear Learning in Rats

Abstract: Alarm pheromones alert conspecifics to the presence of danger. Can pheromone communication aid in learning specific cues? Such facilitation has an evident evolutionary advantage. We use two associative learning paradigms to test this hypothesis. The first is stressed cage mate-induced conditioning. One pair-housed adult rat received 4 pairings of terpinene + shock over 30 min. Ten minutes after return to the home cage, its companion rat was removed and exposed to terpinene. Single-housed controls were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
0
13
1
Order By: Relevance
“…Our findings differ from prior works suggesting that in newborn rabbits 5 and in adult rats 3 , 4 , pheromone components can substitute unconditioned stimuli and mediate learning when paired with conditioned odorants or context. In our work, pheromonal components were neither present during learning, nor did we show that GER or 2H replace sucrose.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings differ from prior works suggesting that in newborn rabbits 5 and in adult rats 3 , 4 , pheromone components can substitute unconditioned stimuli and mediate learning when paired with conditioned odorants or context. In our work, pheromonal components were neither present during learning, nor did we show that GER or 2H replace sucrose.…”
Section: Discussioncontrasting
confidence: 99%
“…In particular, if exposure to pheromones affects in a durable way subsequent associative learning and memory remains unknown. Research on rodents 3 , 4 and rabbits 5 has shown that some pheromone components can replace reinforcing stimuli during associative conditioning and mediate the learning of odor or contextual cues. In contrast to these works, we asked if prior exposure to pheromone components induces subsequent and persistent motivational changes affecting the way in which animals learn and memorize when the pheromone signals are no longer present.…”
Section: Introductionmentioning
confidence: 99%
“…As such, social context profoundly affects vertebrate learning. For example, alarm pheromones are known to enhance fear conditioning in rats, which is mediated by norepinephrine signalling 135 . Zebra finch song learning is another classic example where social context affects learning in vertebrates.…”
Section: Bridging Neuromodulation In Invertebrate and Vertebrate Learmentioning
confidence: 99%
“…For example, alarm pheromones are known to enhance fear conditioning in rats, which is mediated by norepinephrine signalling. 135 Zebra finch song learning is another classic example where social context affects learning in vertebrates. Socially interacting zebra finches perform better at song learning than those that are kept from interacting, an effect mediated by dopamine release upon social interactions.…”
Section: Reproductive Contextmentioning
confidence: 99%
“…However, just as the caregiver may buffer stress, the caregiver is also well positioned to exacerbate or transmit stress to the infant in contexts of increased adversity. Rodent research has demonstrated that caregivers can communicate information about threat via social exchanges, including from mothers to her pups, via CORT-mediated mechanisms (Carew et al, 2018; Debiec & Sullivan, 2014; Keum & Shin, 2019; Monfils & Agee, 2019; Rickenbacher, Perry, Sullivan, & Moita, 2017). Similar human research has documented social transmission of stress from mother to infants (Halevi et al, 2017; Hibel, Trumbell, Valentino, & Buhler-Wassmann, 2018; Hibel, Mercado, & Valentino, 2019; Waters et al, 2014).…”
Section: Discussionmentioning
confidence: 99%